Serum alpha-CGRP levels are increased in COVID-19 patients with headache indicating an activation of the trigeminal system - Gabriel Gárate; María Toriello; Vicente González-Quintanilla; Sara Pérez-Pereda; Jorge Madera; Marta Pascual; José Manuel Olmos; Julio Pascual (BMC Neurology, 2023)
Abstract Background Headache is among the most frequent symptoms of acute COVID-19 infection. Its mechanisms remain obscure, but due to its migraine-like characteristics, the activation of the trigeminal system could account for its underlying pathophysiology. Methods Our aim was to compare the serum levels of CGRP, as a theoretical marker of trigemino-vascular activation, in 25 COVID-19 inpatients with lung involvement experiencing headache, against 15 COVID-19 inpatients without headache and with those of 25 matched healthy controls with no headache history. Results Morning serum alpha-CGRP levels, as measured by ELISA (Abbexa, UK), were increased in COVID-19 patients with headache (55.2±34.3 pg/mL) vs. controls (33.9±14.0 pg/mL) (p < 0.01). Alpha-CGRP levels in COVID-19 patients without headache were also significantly increased (43.3 ± 12.8 pg/mL; p = 0.05) versus healthy controls, but were numerically lower (-28.2%; p = 0.36) as compared to COVID-19 patients with headache. Conclusion CGRP levels are increased in COVID-19 patients experiencing headache in the acute phase of this disease, which could explain why headache frequently occurs in COVID-19 and strongly supports a role for trigeminal activation in the pathophysiology of headache in this viral infection.